2008
DOI: 10.2166/wst.2008.428
|View full text |Cite
|
Sign up to set email alerts
|

Alternative water sources and endotoxin

Abstract: The primary objective of this preliminary study was to ascertain the concentration of endotoxin in a variety of Australian water types, including recycled water. A total of 42 sampling sites were surveyed, the majority on at least 2 separate occasions (total number of samples analysed was 76). Samples were collected from a variety of locations throughout Australia including: drinking water distribution (12), drinking water reservoir (4), wastewater treatment train (11) and finished recycled water (15). Class A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Information on endotoxin levels in various water samples has been accumulated. Just as an example, drinking water in Japan, China, and Australia ranges 1e10, 4e10, and 72e186 EU/ mL, respectively, while the endotoxin levels in source water varied largely, but normally are in the range of 10e1000 EU/mL (Ohkouchi et al, 2007(Ohkouchi et al, , 2009Can et al, 2013;O'Toole et al, 2008). Rapala et al (2002) also reported that water bloom sample with dense cyanobacteria reached at 3.8 Â 10 4 EU/mL in Finland.…”
Section: Introductionmentioning
confidence: 99%
“…Information on endotoxin levels in various water samples has been accumulated. Just as an example, drinking water in Japan, China, and Australia ranges 1e10, 4e10, and 72e186 EU/ mL, respectively, while the endotoxin levels in source water varied largely, but normally are in the range of 10e1000 EU/mL (Ohkouchi et al, 2007(Ohkouchi et al, , 2009Can et al, 2013;O'Toole et al, 2008). Rapala et al (2002) also reported that water bloom sample with dense cyanobacteria reached at 3.8 Â 10 4 EU/mL in Finland.…”
Section: Introductionmentioning
confidence: 99%
“…Carcinogenic, hormonal, heavy metal and radiological effects must be considered for treatment of recycled water for drinking purposes [105,106] but chronic effects to low levels of chemicals are not well understood, requiring further research [106]. …”
Section: Heavy Metals Chemicals Hormones and Endocrine-disruptinmentioning
confidence: 99%
“…Bacterial lipopolysaccharides (LPS) are well-known NF-κB activators (Sen and Baltimore, 1986), and endotoxins, which are naturally occurring complex LPS, are present in surface water and wastewater (O'Toole et al, 2008). Studies have related inflammatory responses in vitro to endotoxin concentrations in whole water samples (Wichmann et al, 2004;El Marghani et al, 2014), but few have considered SPE extracts.…”
Section: Introductionmentioning
confidence: 99%